State-owned enterprises leverage as a contingency in public debt sustainability analysis: The case of the People's Republic of China - Benno Ferrarini; Marthe Hinojales (Asian Development Bank (ADB), 2018)
We reflect state-owned enterprises' (SOE) leverage within the standard debt sustainability assessment framework. Based on company data and the interest coverage ratio as a measure of debt at risk, aggregate baseline projections and fan charts gauge SOE debt as a contingent liability to the public sector. We find that SOE leverage in the People's Republic of China has grown to a large liability that deserves the urgent attention it has been receiving from the authorities. While there is no room for complacency, there is no need for panic either; even if authorities had to step into mop up as much as 20% of SOE debt at risk gone bad, this would appear to be manageable at roughly 2.7% of the gross domestic product in 2016 or 5.5% by 2021. These findings are reflective of discretionary assumptions about future developments in the SOE sector and the broader economy - including baseline conditions premised on preventive government action to slow borrowing - that are adjustable to reflect analysts' prerogatives and expectations.
Keywords: G01; G21; H30; H60; 330; contingent liabilities; corporate leverage; People's Republic of China; public debt sustainability; state-owned enterprises